Mobilization of mercury by sediment transport after a prescribed fire in NE Portugal: Insight into size classes and temporal variation - Méndez-López, Melissa (2025)
Terrestrial ecosystems are important sinks for atmospheric mercury (Hg). It is well known that high severity wildfires can mobilize Hg in the surroundings of burned areas due to changes in ecosystem stability, but it is unclear whether this also occurs after lower severity fires, such as prescribed fires. The present study determined Hg concentrations and mobilization rates in different size fractions of sediments collected after a prescribed fire in a scrubland area. Sediments, collected from eight erosion plots on six occasions, were analysed for total Hg, C and N in several size classes (<0.2 mm, 0.2–0.5 mm, 0.5–2 mm and >2 mm) and Hg mobilization rates (HgST) were calculated for each size fraction. Average total Hg were 38, 57, 94 and 126 μg kg^-1 for size fractions > 2, 0.5–2, 0.2–0.5 and < 0.2 mm, respectively. Total Hg was negatively correlated with C/N ratio, involving the humification degree of organic matter of sediments in Hg retention. In the last event (eight months after fire), sediments had 45–106 % more Hg, depending on size fraction, compared to the initial event. Mercury mobilization rates varied between 32 and 78 mg ha^-1, with the fraction 0.5–2 mm accounting for 46 % of the mobilized Hg. The results revealed that prescribed fires can mobilize Hg, so their use to prevent wildfires must be done with caution.